Ilizarov Treatment Protocols in the Management of Infected Nonunion of the Tibia. Issue 5 (October 2017) - McNally, Martin; Ferguson, Jamie; Kugan, Raj; Stubbs, David
Abstract : Objectives: We present a treatment algorithm comprising 4 Ilizarov methods in managing infected tibial nonunion, using nonunion mobility and segmental defect size to govern treatment choice. Design: Decision protocol analysis study. Setting: A university-affiliated teaching hospital. Patients/Participants: Seventy-nine patients were treated with 1 of 4 Ilizarov protocols. All patients had undergone at least one previous operation, 38 had associated limb deformity, and 49 had nonviable nonunions. Twenty-six had a new muscle flap at the time of Ilizarov surgery, and 25 had preexisting flaps reused. Intervention: Twenty-six cases were treated with monofocal distraction, 19 with monofocal compression, 16 with bifocal compression/distraction, and 18 with bone transport. Main Outcome Measurements: The primary outcome measure was the absence of recurrent infection. Secondary outcomes included bone union, complications, the Association for the Advancement of Methods of Ilizarov (ASAMI) bone and functional classification scores, and any need for further unplanned surgery. Results: Infection was eradicated in 76 cases (96.2%) with a mean follow-up duration of 40.8 months (range 6–131). All 3 infection recurrences occurred in the monofocal compression group. Following the initial Ilizarov method alone, union was achieved in 68 cases (86.1%) and was highest among the monofocal distraction (96.2%) and bifocal compression/distraction groups (93.8%). Monofocal compression achieved the lowest union rate (73.7%), significantly lower ASAMI scores, and a refracture rate of 31.6%. Bone transport secured union in 77.8% with a 44.4% unplanned reoperation rate. However, infection-free union was 100% after further treatment. Conclusions: Monofocal compression is not recommended for treating infected, mobile nonunions. Distraction (monofocal or bifocal) was effective and achieved higher rates of union and infection clearance. Level of Evidence: Level III. Abstract : Supplemental Digital Content is Available in the Text.